Synthesis and electrochemical investigation of spinel cobalt ferrite magnetic nanoparticles for supercapacitor application - H. Kennaz, A. Harat, O. Guellati, D. Y. Momodu, F. Barzegar, J. K. Dangbegnon, N. Manyala, M. Guerioune (J Solid State Electrochem, 2018)
Cobalt ferrite magnetic nanoparticles (CoFe2O4- MNPs) were synthesized by hydrothermal and coprecipitation methods using different precursors such as nitrates, chlorides, and acetates, at different concentrations with/without surfactant under different growth conditions. The structural and morphological analyses reveal the formation of a single-phase CoFe2O4 in nanoplatelet-shaped NPs with average particle size between 11 and 26 nm depending on synthesis condition. The specific surface area of these NPs obtained by hydrothermal method was ~ 34 m2 g−1. Electrochemical performances of the obtained nanoparticles in a three-electrode configuration with a 6 M KOH electrolyte revealed a specific capacitance (Cs) of 429 F/g at 0.5 A/g, with excellent capacitance retention of 98.8% after 6000 cycles at 10 A/g for the electroactive NPs synthesized by hydrothermal method at 200 °C for 18 h.